Sejarah Pembinaan terhadap Suku Anak Dalam di Kabupaten Batanghari Provinsi Jambi (1970-2014) - Ferry Yanto (Universitas Batanghari Jambi, 2019)
The focus of the problem in this study is to analyze the coaching process carried out by the Government and NGOs. The phenomenon of forest conversion into large oil palm plantations has eliminated the source of livelihoods of the SAD community, which largely depends on forest products. Transfer of land functions also caused some SAD out of their original home range and made SAD fragmented and formed groups with new identities. The study was conducted using historical research methods with a socio-cultural approach. The use of development theory is needed to support the writing of this thesis. From the results of the study it was found that the impact of the formation and effect of the conversion of forest functions which were used as large oil palm plantations and settlements of transmigrants during the New Order changed some SAD communities to shift their livelihoods, change their mindset, broaden their traditions and culture of origin and shape their origin a new identity. After entering the period of Regional Autonomy, the SAD people who were initially silent and accepted all the policies that came from the Central Government, now become a tough person and oppose all the injustices that were perpetrated by the New Order Government. SAD began to demand customary rights in the form of customary land which affected the next Government.